The i-gel Supraglottic Airway as a Conduit for Fibreoptic Tracheal Intubation – A Randomized Comparison with the Single-use Intubating Laryngeal Mask Airway and CTrach Laryngeal Mask in Patients with Predicted Difficult Laryngoscopy - Pavel Michálek (Prague Medical Report, 2016)
Fibreoptic intubation through a supraglottic airway is an alternative plan for airway management in difficult or failed laryngoscopy. The aim of this study was to compare three supraglottic airways as conduits in patients with at least one predictor for difficult laryngoscopy. The i-gel was compared with the single-use intubating laryngeal mask airway (sILMA) and CTrach laryngeal mask in 120 adult patients scheduled for elective surgeries under general anaesthesia using a prospective, randomized and single-blinded design. Primary outcome was success rate of tracheal intubation through the device, while secondary outcomes were times required for device insertion and tracheal tube placement, fibreoptic scores and the incidence of perioperative complications and postoperative complaints. The success rates showed no statistical difference between devices (i-gel 100%, CTrach 97.5%, ILMA 95%). Insertion time was shortest for the i-gel (12.4 s) compared with ILMA (19.3 s) and CTrach (24.4 s). Intubation time was shorter in the i-gel group (29.4 s) in comparison with the CTrach (39.8 s, p<0.05) and sILMA (51.9 s, p<0.001) groups. Best fibreoptic scores were observed also in the i-gel group. In total, 24 patients (20%) presented with difficult laryngoscopy. The i-gel showed significantly shorter times for insertion and fibreoptic intubation than the other two devices in this group. No difference was observed in the incidence of postoperative complaints. The i-gel is a suitable alternative to the sILMA and CTrach for fibrescope-guided tracheal intubation. Shorter insertion and intubation times with the i-gel may provide advantage in case of difficult oxygenation.